The Effect of Management Control Systems and Reward Policies on Employee Performance - Muhamad Solehudin; Uswatun Hasanah; Indri Utami (Business Management, 2026)
This study aims to analyze the effect of management control systems and reward policies on employee performance at the Regional Personnel and Human Resources Development Agency (BKPSDM) of Bandung Regency. This study employed a quantitative approach using descriptive and verification methods. Primary data were collected through questionnaires distributed to 37 employees selected using simple random sampling. Data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results indicate that management control systems and reward policies have a significant effects on employee performance. Simultaneously, both variables explain 71% of the variation in employee performance, while the remaining 29% is influenced by other factors outside the research model. These findings indicate that effective management control systems and appropriate reward policies play important roles in improving employee performance within public sector organizations.